Career & Work Aspirations: Assessment of Work Competencies and Interests as a Basis for Employee Career Planning - Ramadhani Lucky Al Kahfi; Rosatyani Puspita Adiyati (Psikostudia : Jurnal Psikologi, 2023)
Organizations are always faced with uncertainty, and they are expected to make adjustments in order to survive. Humans are slowly perceived as an important asset, so today's HR practices are beginning to focus on empowering employees. Managing human resources are not only covers on education and training, but also career planning. Unfortunately, not all organizations are aware about the fitness between employees and their jobs, when preparing career plans for them. Unfitness of employee with their work can harm organizational performance, if not addressed properly. This research is intended to see the fitness between employees’ competence and work interest, with their career aspirations. A research participant is an employee with 3 years of work experience, who is affected by organizations restructured. Research was conducted using a descriptive qualitative method, using assessment instruments to collect the data. The results show that the subject's competence and work interest are sufficient in accordance with one of the career choices, but developments are still needed in order to the success doing the job.Organisasi selalu dihadapkan pada ketidakpastian, dan diharapkan melakukan penyesuaian agar tetap dapat bertahan. Manusia perlahan dipandang sebagai aset penting, hingga praktik SDM saat ini mulai berfokus pada pemberdayaan karyawan. Pengelolaan SDM tidak hanya meliputi pendidikan dan pelatihan, namun juga perencanaan karir. Sayangnya, belum semua organisasi menaruh perhatian terhadap kesesuaian antara karyawan dan pekerjaannya, dalam penyusunan perencanaan karir untuk karyawan di dalamnya. Ketidaksesuaian karyawan dengan pekerjaannya dapat membahayakan kinerja organisasi, jika tidak segera ditangani. Penelitian ini ditujukan untuk melihat kesesuaian antara kompetensi dan minat kerja karyawan, dengan aspirasi karir dari karyawan. Subjek merupakan karyawan dengan masa kerja 3 tahun, yang terdampak oleh restrukturisasi. Penelitian dilakukan menggunakan metode kualitatif deskriptif, menggunakan instrumen asesmen dalam pengambilan datanya. Hasil penelitian menunjukkan bahwa komopetensi dan minat kerja subjek sudah cukup sesuai dengan salah satu pilihan karirnya, namun masih diperlukan pengembangan agar subjek berhasil dalam pekerjaan tersebut.